2019
DOI: 10.1111/bjd.17511
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain diagnosis and prognosis in advanced melanoma: a qualitative study of the experiences of bereaved carers in a time of immune and targeted therapies

Abstract: Summary Background Recent advances in advanced melanoma therapies are associated with improved survival for some patients. However, how patients with diagnoses of advanced disease and their carers experience this expanding treatment paradigm is not well understood. Objectives To explore bereaved carers’ accounts of the trajectory of advanced melanoma involving treatment by immune or targeted therapies, to build an understanding of their experiences of care relating to diagnosis and prognosis. Methods A qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…24 47 Indeed, patients reported feeling hampered by a lack of clear information, 23 and carers experienced unclear communication regarding immunotherapy treatment. 47 Findings from a recent study 48 indicated that most recommendations for ICI treatment were made by physicians, though patients generally preferred to have the final say regarding treatment commencement. Further enquiry is therefore required to explore both patients' and healthcare professionals' experiences of immunotherapy treatment decision-making in the context of the UK.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…24 47 Indeed, patients reported feeling hampered by a lack of clear information, 23 and carers experienced unclear communication regarding immunotherapy treatment. 47 Findings from a recent study 48 indicated that most recommendations for ICI treatment were made by physicians, though patients generally preferred to have the final say regarding treatment commencement. Further enquiry is therefore required to explore both patients' and healthcare professionals' experiences of immunotherapy treatment decision-making in the context of the UK.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…21 Patients/carers and clinicians navigate a complex disease trajectory 22 and face ongoing uncertainty regarding prognosis, progression, treatment and possible outcomes. 8,23 Uncertainty adds to healthcare system fragmentation and lack of coordination. 6,24,25 Previously, therapeutic and end-of-life discussions concerning metastatic melanoma were framed around poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Authors responded to our challenge with a wider range of submissions and almost double the number submitted last time, showing the growing interest in qualitative research in this field. Our second spotlight for summer 2019 showcases 10 studies, comprising a complementary mix of six original articles and four research letters . These papers involve interdisciplinary authorship teams from dermatology, psychology, general practice, nursing, public health and applied health services research in Australia, Germany, the Netherlands, the Republic of Ireland, the U.K. and the U.S.A.…”
mentioning
confidence: 99%
“…Six papers, demonstrate qualitative methods’ capacity to access psychological and social issues that are difficult to reach with traditional questionnaire/survey research, and the capability to investigate the portrayal and experience of the skin in the online world. Fox et al . explored the unique perspective of carers on their journey through advanced melanoma diagnosis, death and bereavement.…”
mentioning
confidence: 99%
See 1 more Smart Citation